Quality Management of Package C Graduates Through Non-Formal Education Accreditation Program - Ayi Abdurahman (UIN Sunan Gunung Djati Bandung, 2021)
The background of this research is that the synchronization between the results of the accreditation assessment and the quality of the graduates of Package C is not optimal. The focus of the problem in this study is that the management of the learning process is still not optimal in accordance with the eight national education standards. This happens because of the lack of interest in learning from students, non-linear competence of tutors and tutors, unrepresentative infrastructure, lack of funding, and management discipline. This study aims to determine the quality planning of graduates, implementation strategies, evaluation, potential, obstacles, controls and outcomes for the quality of graduates. The theory that underlies this research is integrated quality management. The approach used in this research is a qualitative approach and data collection techniques through observation, interviews, documentation studies, and literature studies. The conclusion of this study is that the management of the learning process has not been able to meet the eight national education standards so that the quality of graduates is not optimal.